INMT: Interactive Neural Machine Translation Prediction - Santy, Sebastin; Dandapat, Sandipan; Choudhury, Monojit; Bali, Kalika (2019 Empirical Methods in Natural Language Processing, 2019)
In this paper, we demonstrate an Interactive Machine Translation interface, that assists human translators with on-the-fly hints and suggestions. This makes the end-to-end translation process faster, more efficient and creates high-quality translations. We augment the OpenNMT backend with a mechanism to accept the user input and generate conditioned translations.